Challenges in Purposive Communication and Macro Skills of Students - Ruby Kristine H. Olaño; Sherell M. Bue (Future Science / FSH-PH Publications, 2025)
This study examined the communication challenges and macro skill proficiency of third-year Purposive Communication students at the Bicol State College of Applied Sciences and Technology (BISCAST) during the first semester of SY 2024–2025. Using a descriptive-comparative-correlational design, data were collected from 152 students across four programs through using IELTS mock tests and researcher-made questionnaires. Findings revealed that students struggled most with understanding main ideas and inferencing, followed by critical thinking, lexical resource and vocabulary, reading strategies, and grammatical range accuracy. All macro skills were all at developing levels except viewing, which found to be in Good level; revealing listening to be the weakest and viewing as the strongest. There were significant performance differences found across paired macro skills with listening varying significantly among other macro skills and across paired programs with Bachelor of Science in Civil Engineering [BSCE] students performing the strongest and Bachelor of Engineering Technology Major in Mechanical Automotive Engineering Technology [BET-MAET] performing the weakest. The study found a significant correlation of about 47.9% variance showing that students who faced greater communicative challenges are also likely to have lower macro skill proficiency. Strategies employed in reading, critical thinking, and grammatical skills proved to have moderate effects on majority of the macro skills but proved to have very weak influence on reading, interestingly as it is also the least influenced skill.